2021
DOI: 10.1186/s42523-020-00064-2
|View full text |Cite
|
Sign up to set email alerts
|

Oregano essential oil improves piglet health and performance through maternal feeding and is associated with changes in the gut microbiota

Abstract: Background With a growing demand for safe and sustainable alternatives to antimicrobials, functional feed ingredients such as plant essential oils have been evaluated for their potential to improve gut health. Amongst these, oregano essential oil (OEO) with the main active compounds carvacrol and thymol has been reported to have antimicrobial and antioxidative properties resulting in improved intestinal barrier function and growth in pigs and poultry. However, its impact on the gut microbiota s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 75 publications
(97 reference statements)
0
21
0
Order By: Relevance
“…(2018) reported that oregano essential oil (OEO) reduced E. coli counts in the ileal digesta and improved intestinal morphology, the antioxidative capacity, and growth performance of growing-finishing pigs. Furthermore, the offspring of sows fed diets containing OEO during late gestation and lactation had improved growth performance and health due to the modulation of the fecal microbiota ( Hall et al., 2021 ). Piglets from sows fed diets with OEO increased the abundance of Spirochaetaceae , Peptostreptococcaceae, Ruminococcaceae, Erysipelotrichacea, and Lachnospiraceae in feces ( Table 1 ).…”
Section: Interaction Among Diets Microbiota and Immune Systemmentioning
confidence: 99%
“…(2018) reported that oregano essential oil (OEO) reduced E. coli counts in the ileal digesta and improved intestinal morphology, the antioxidative capacity, and growth performance of growing-finishing pigs. Furthermore, the offspring of sows fed diets containing OEO during late gestation and lactation had improved growth performance and health due to the modulation of the fecal microbiota ( Hall et al., 2021 ). Piglets from sows fed diets with OEO increased the abundance of Spirochaetaceae , Peptostreptococcaceae, Ruminococcaceae, Erysipelotrichacea, and Lachnospiraceae in feces ( Table 1 ).…”
Section: Interaction Among Diets Microbiota and Immune Systemmentioning
confidence: 99%
“…It has been reported that OEO exerts antimicrobial and antioxidative ability to improve intestinal barrier function and growth in pigs. OEO supplementation to maternal rations during late gestation and lactation can lead to improvements in progeny health and performance with a reduced incidence of mortality and lower need for medication ( 62 ). The main active compounds carvacrol and thymol in OEO possess ROS-scavenging activity in vitro .…”
Section: Pharmacological Applications Of Phytochemicals In Pig Productionmentioning
confidence: 99%
“…The OEO-treated pigs show decreased endotoxin levels in serum and increased villus height and the expression of Occludin and Zonula occludens-1 (ZO-1) in the jejunum ( 83 ). The main active compounds carvacrol and thymol in OEO contribute to have antimicrobial and antioxidative capacity to improve intestinal barrier function and growth in pigs ( 62 ). In addition, supplementation of AGP or microencapsulated organic acids (OA) and EO does not significantly attenuate the induced inflammation, reduce digestive enzyme activities, and elevate gut permeability in piglets infected with Escherichia coli F4 (ETEC F4) in weaned piglets ( 84 ).…”
Section: Pharmacological Applications Of Phytochemicals In Pig Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…OEO as an antibiotic growth promoter alternative on growth performance, antioxidant status, and intestinal health of broilers (Zhang et al 2021). OEO improves piglet health and performance through maternal feeding and is associated with changes in the gut microbiota (Hall et al 2021). The intestinal lumen is the main site colonised by bacteria and other microorganisms (Yadav et al 2018).…”
Section: Introductionmentioning
confidence: 99%